Factors affecting the profitability of small businesses and manufacturing enterprises - Izzatullayeva Madinabonu Yolqin qizi (THE INNOVATION ECONOMY, 2026)
This article examines ways to improve the efficiency of small businesses and manufacturing enterprises within the framework of Uzbekistan’s economic stability, as well as the possibilities for shaping economic policy. In addition, the advantages of using regression analysis, profitability indicators, and Cobb-Douglas functions in studying the interrelation of economic indicators are analyzed. Based on scientific sources, the main directions for achieving enterprise efficiency in the context of contemporary innovative development are also highlighted.